Design and implementation of a microcontroller based electrostatic spray pyrolysis instrument for thin film deposition - Ojonugwa Daniel, Thomas; Alu, Noble; Oreoluwa Edaogbogun, Goodness; Olajid, Abdulmutolib; Amah, Orji (International Journal of Physical Research, 2022)
This research is focused on the design and implementation of a microcontroller based electrostatic spray pyrolysis instrument that can sense and regulate temperature change with an alternating current to direct current converter in the range of 220V-1KV AC to 20KV DC for thin film deposition. In spray pyrolysis technique precise management of the spray parameters helps to create good and uniform thin films with ease of reproducibility of film properties. However it is a draw back in the manually operated electrostatic spray pyrolysis instrument mostly used in developing countries of Africa which causes variations in film structure, thickness, associated film properties and difficulty of reproducibility of film properties. The need for improved locally made ESP unit is also timely due to the inadequacy/unavailability of thin film deposition apparatus in most African institutions/materials research laboratories. The circuit was simulated on Multism software and transfer to PCB, etching was done using Lead (II) oxide while the unit components where assembled by soldering of electronics components, bonding and drilling of associated components. Arduinounoatmega 328 micro controller was employed. The fabricated device operated at 1KV to 20KV dc voltage for film deposition, at a substrate temperature range of 100oC to 450oC with a steady flow rate of 0.04ml/min, define spray pattern, define precursor usage and a precise control of major deposition parameters. ZnO:Al thin film deposited with the equipment was found to have a crystalline structure of fine grains.Â Â Â